Bargaining power and biofortification: The role of gender in adoption of orange sweet potato in Uganda - Gilligan, Daniel O.; Kumar, Neha; McNiven, Scott; Meenakshi, Jonnalagadda V.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2014)
We examine the role of gender in adoption and diffusion of orange sweet potato, a biofortified staple food crop being promoted as a strategy to increase dietary intakes of vitamin A among young children and adult women in Uganda. As an agricultural intervention with nutrition objectives, intrahousehold gender dynamics regarding decisions about crop choice and child feeding practices may play a role in adoption decisions. Also, most households access sweet potato vines through informal exchange, suggesting again that gender dimensions of networks may be important to diffusion of the crop. We use data from an experimental impact evaluation of the introduction of OSP in Uganda to study how female bargaining power, measured by share of land and nonland assets controlled by women, affect adoption and diffusion decisions. We find that the share of assets controlled by women does not affect the probability of adopting OSP at the household level. In examining adoption decisions within households, plots of land exclusively controlled by women are not more likely to contain OSP, but plots under joint control of men and women, in which a woman has primary control over decisionmaking are significantly more likely to contain OSP. Plots exclusively controlled by men are the least likely to contain OSP. Also, we find that the share of nonland assets controlled by women increases dietary intakes of vitamin A, but this measure of female bargaining power does not increase the impact of the OSP project on vitamin A, suggesting that the project had similar impacts across households with different levels of female bargaining power.